Genetic Monogamy in Socially Monogamous Mammals Is Primarily Predicted by Multiple Life History Factors: A Meta-Analysis - Lambert, Connor T.; Sabol, Anne C.; Solomon, Nancy G. (Frontiers in Ecology and Evolution, 2018)
Background We still do not understand the key drivers or prevalence of genetic monogamy in mammals despite the amount of attention that the evolution of mammalian monogamy has received. There have been numerous reviews of the hypotheses proposed to explain monogamy, some of which focused on animals in general, while others focused on particular classes like birds or mammals, or on specific orders within a class. Because monogamy is rare in mammals overall but relatively common in some of the orders in which it has been observed (e.g., Primates, Macroscelidea and Carnivora), mammals provide a unique taxon in which to study the evolution and maintenance of monogamy However, the term ‘monogamy’ encompasses related but separate phenomena; i.e., social monogamy (pair-living by opposite-sex conspecifics) and genetic monogamy or reproductive monogamy (mating exclusivity). A recent review of mammalian monogamy reported that 226 species (9%) in 9 orders (35%) were socially monogamous, although socially monogamous mammals are not necessarily genetically monogamous. Methods Since factors that predispose socially monogamous mammals to be genetically monogamous are still subject to debate, we conducted meta-analyses using model selection to determine the relative importance of several life history, demographic and environmental factors in predicting genetic monogamy. Results We found sufficient data to include 41 species in our analysis, about 2x more than have been included in previous analyses of mammalian genetic monogamy. We found that living as part of a socially monogamous pair versus in a group was the best predictor of genetic monogamy, either by itself or in combination with high levels of paternal care. A male-biased sex ratio and low population density were inversely related to the number of pairs that were genetically monogamous, but not to the production of intra-pair young or litters. Conclusion Our results agree with the results of some previous analyses but suggest that more than one factor may be important in driving genetic monogamy in mammals.